Peran Guru IPS dalam Pembelajaran Ramah Anak untuk Mewujudkan Tujuan Global yang Berkelanjutan (SDGs 4) - Fauzi, Imran; Fredy Hermanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the role of Social Studies (IPS) teachers in implementing child-friendly learning and to examine its contribution to supporting the Child-Friendly School (CFS) program and the achievement of Sustainable Development Goal (SDG) 4 on quality education. This study employed a qualitative approach with a case study design conducted at SMP Negeri 12 Semarang, one of the award-winning Child-Friendly Schools in Semarang City. Data were collected through in-depth interviews, classroom observations, and document analysis, and were analyzed using the interactive model of Miles and Huberman. The findings reveal that Social Studies teachers play a strategic role in creating a safe and non-violent learning environment, promoting participatory and inclusive learning, respecting diversity, and implementing fair and holistic assessment practices. These child-friendly learning practices not only support the fulfillment of children's rights but also strengthen students' character development, including responsibility, tolerance, and social awareness. The study concludes that the role of Social Studies teachers is a key factor in the successful implementation of child-friendly learning, thereby fostering a school culture that prioritizes children's rights and enhances the quality of sustainable education. Keywords: Character Educatio, Child-Friendly School, Inclusive Learning, SDGs 4, Social Studies Teacher.